2002
DOI: 10.5194/aab-45-349-2002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of time of day the milk and season on the somatic cell count under Hungarian conditions

Abstract: Abstract. This research indicates that the numerical value of the emptying of somatic cells as a result of the effect of time of day cannot be demonstrated and interval difference less than 2 hours between milking does not significantly influence the formation of somatic cells and their absolute quantity. Moreover it was confirmed that subclinical mastitis also occurs in individual udder quarters of healthy qualified cows producing bulk milk with somatic cell count below 400 thousand / ml. Udder quarter with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The effect of continued use of machine-milking on the cow's udder and teats cannot be underestimated. The quarter position significantly (p<0.001) influenced the SCS of the cows (BALTAY, 2002). It was found that the quarter in the right rear position of the udder had the lowest score of 3.33, whereas the others had values ranging from 3.55 to 3.60.…”
Section: Milk Componentsmentioning
confidence: 84%
“…The effect of continued use of machine-milking on the cow's udder and teats cannot be underestimated. The quarter position significantly (p<0.001) influenced the SCS of the cows (BALTAY, 2002). It was found that the quarter in the right rear position of the udder had the lowest score of 3.33, whereas the others had values ranging from 3.55 to 3.60.…”
Section: Milk Componentsmentioning
confidence: 84%
“…In this condition, the metabolic activity was affected to a slight extent by heat stress, and milk yield could decrease. Generally, high ambient temperatures depressively affect milk production (Johnson 1986;BALTAY, 2002;Soch, 2005). However, the effects of hot environment on milk production vary with the LS.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, differences in rainfall and climatic conditions in different regions of Iran and even in different years can lead to different results. In countries where calving occurs throughout the year, mastitis is dependent to the pattern of growth of pathogens in different seasons and years (Baltay 2002). But when seasonal conditions are not conducive to the growth of microorganisms, changes in animal physiological conditions (such as calving and changes in breast status) increase the number of somatic cells in milk, which has a physiological effect.…”
Section: Resultsmentioning
confidence: 99%